Knowledge, attitude and practices for antenatal care, danger signs of pregnancy and family planning among pregnant women in a rural area of Kerala, India - John, Nimmy N.; George, Amrutha (International Journal Of Community Medicine And Public Health, 2020)
Background: Maternal health services have a potentially critical role in the improvement of reproductive health. The use of health service related to availability, quality and cost of services as well as the social structures, health beliefs and personal characteristics of the users. Objective was to determine the level of knowledge, attitude, and practice related to antenatal care (ANC), danger signs and family planning among the pregnant women. Methods: This cross-sectional study was carried out in May 2020 to August 2020 in a rural area of Thrissur district of Kerala, India. 150 pregnant women (aged 18‑35 years) attending the antenatal clinics were interviewed using a predesigned, pretested questionnaire. Results: The knowledge and attitude of the participants towards antenatal care, danger signs of pregnancy and adopting family planning methods was adequate in the study population. The total score of knowledge was 80%, positive attitude was 91% and practice was 77%. The participants also had knowledge regarding pregnancy danger signs. Nearly 92% were aware of bleeding per vagina being a danger sign, 85% stated weak or no movement of baby as a danger sign, 75% knew that pain in abdomen was a danger, 68% knew excessive vomiting as a danger sign while a mere 41% reported that convulsions were a danger sign. Conclusions: The role of health workers in increasing awareness among mothers about the importance of ANC, the danger signs of pregnancy and adopting family planning methods are of paramount concern.